All-fiber optical parametric oscillator for bio-medical imaging applications - Gottschall, Thomas; Meyer, Tobias; Jauregui, Cesar; Just, Florian; Eidam, Tino; Schmitt, Michael; Popp, Jürgen; Limpert, Jens; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Among other modern imaging techniques, stimulated Raman Scattering (SRS) requires an extremely quiet, widely wavelength tunable laser, which, up to now, is unheard of in fiber laser systems. We present a compact all-fiber laser system, which features an optical parametric oscillator (OPO) based on degenerate four-wave mixing (FWM) in an endlessly single-mode photonic-crystal fiber. We employ an all-fiber frequency and repetition rate tunable laser in order to enable wideband conversion in the linear OPO cavity arrangement, the signal and idler radiation can be tuned between 764 and 960 nm and 1164 and 1552 nm at 9.5 MHz. Thus, all biochemically relevant Raman shifts between 922 and 3322 cm-1 may be addressed in combination with a secondary output, which is tunable between 1024 and 1052 nm. This ultra-low noise output emits synchronized pulses with twice the repetition rate to enable SRS imaging. We measure the relative intensity noise of this output beam at 9.5 MHz to be between -145 and -148 dBc, which is low enough to enable high-speed SRS imaging with a good signal-to-noise ratio. The laser system is computer controlled to access a certain energy differences within one second. Combining FWM based conversion, with all-fiber Yb-based fiber lasers enables the construction of the first automated, turn-key and widely tunable fiber laser. This laser concept could be the missing piece to establish CRS imaging as a reliable guiding tool for clinical diagnostics and surgical guidance.
CRIS-Team Scopus Importer:2023-04-20
Keywords: (140.3510) Lasers; fiber; (180.4315) Nonlinear microscopy; (190.4370) Nonlinear optics; fibers; Four-wave mixing; Nonlinear optics